2014
DOI: 10.1088/0004-637x/795/2/106
|View full text |Cite
|
Sign up to set email alerts
|

A Helium-Carbon Correlation on the Extreme Horizontal Branch in Ω Centauri

Abstract: Taking advantage of a recent FORS2/VLT spectroscopic sample of Extreme Horizontal Branch (EHB) stars in ω Cen, we isolate 38 spectra well suited for detailed atmospheric studies and determine their fundamental parameters (T eff , log g, and log N (He)/N (H)) using NLTE, metal line-blanketed models. We find that our targets can be divided into three groups: 6 stars are hot (T eff > ∼ 45,000 K) H-rich subdwarf O stars, 7 stars are typical H-rich sdB stars (T eff < ∼ 35,000 K), and the remaining 25 targets at int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 51 publications
6
57
0
Order By: Relevance
“…Fig. 11 of Latour et al 2014). It is clear that in order for He-rich sdBs to exist in the numbers observed, diffusion must be slowed down, possibly by internal turbulence or a weak stellar wind, but the details are far from being understood.…”
Section: Resultsmentioning
confidence: 95%
“…Fig. 11 of Latour et al 2014). It is clear that in order for He-rich sdBs to exist in the numbers observed, diffusion must be slowed down, possibly by internal turbulence or a weak stellar wind, but the details are far from being understood.…”
Section: Resultsmentioning
confidence: 95%
“…Depending on the depth of the mixing, stars with more or less helium in the atmospheres and different atmospheric parameters can be formed in this way. Most recently, Latour et al (2014) found a correlation between the carbon and helium abundances of the He-sdOB stars in the globular cluster ω Cen, which is predicted by late hot flasher models. Hirsch (2009) discovered a similar correlation for field helium-rich hot subdwarf (see also Heber & Hirsch 2010).…”
Section: Introductionmentioning
confidence: 84%
“…6) and the atmospheric parameters are quite typical for the field population of He-sdOs (T eff = 40 000−50 000 K, Ströer et al 2007;Nemeth et al 2012). However, quite a number of stars have lower temperatures between 35 000 K and 40 000 K. Those helium-rich sdOBs are rare in the field population, but quite dominant in the globular cluster ω Cen (Latour et al 2014). Following the discussion in Latour et al (2014) this might be related to the age of the parent population, since most of the stars in our sample belong to the old thick disk or halo populations, while most of the bright stars studied by Nemeth et al (2012) belong to the young thin disk population.…”
Section: Irregular Rv Variations Of Helium-rich Hot Subdwarf Starsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additional abundances of carbon and nitrogen were then measured in these sdO stars by Hirsch (2009) and Hirsch & Heber (in prep.). The sample of ω Centauri EHB stars in Moehler et al (2011) and Latour et al (2014c) also included a fair amount of sdO stars, but mostly cooler stars found at the transition between the spectral types B and O 2 A comprehensive review of the global properties and characteristics of hot subdwarf stars can be found in Heber (2009). A&A 579, A39 (2015) (i.e., below 40 000 K).…”
Section: Astrophysical Contextmentioning
confidence: 99%